El clima organizacional y su incidencia en el desempeño laboral del personal administrativo de la Universidad Nacional de Loja - Patiño Calderón, Yadira Soledad (2023)
This investigative work’s general objective was to analyze the incidence of the organizational climate on the work performance of the administrative employees of the Universidad Nacional de Loja in the year 2022, therefore, we proceeded to identify the factors of the organizational climate that influence the foretold staff’s working performance, and the existing correlation. The research was developed with a quantitative cross-sectional approach, non-experimental design, it was established as an inductive, analytical and synthetic descriptive type. The utilized technique was the survey, which was applied to the target population constituted by a total of 299 people, from which a significant sample of 136 people was taken. As an instrument, we used some questions based on the work of Ana Adela López, called "Organizational Climate and Labor Performance: methodological proposal for the Salesian Polytechnic University Guayaquil Headquarters" (López Neira, 2021). Some questions were formulated to identify the factors of the organizational climate that influence work performance, so it was possible to determine the connection between the organizational climate and the work performance of the personnel. To do this, we used the Rho of Spearman test, communication, motivation, leadership and teamwork, with the work performance variable; The results obtained reflected a level of correlation between the variables, thus asserting that the organizational climate does affect the performance of the administrative staff of the Universidad Nacional de Loja, hence some recommendations were made for the University’s authorities, recommendations that benefit the institution.